2014
DOI: 10.1080/13102818.2014.942489
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of ethyl pyruvate in cisplatin-induced nephrotoxicity

Abstract: This study was performed to investigate the effect of ethyl pyruvate on changes in renal functions and oxidative stress related renal injury caused by cisplatin (cis-dichlorodiammine platinum-II; CDDP).Male Wistar albino rats were divided into four groups (n = 8): (1) control group (1 ml Ringer's lactate solution i.p.); (2) ethyl pyruvate (EP) group (50 mg/kg Ringer's EP solution (REPS) i.p.); (3) cisplatin group (a single dose of cisplatin (5 mg/kg, i.p.); and (4) cisplatin + EP group (a single dose of cispla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Likewise, rather than individually determining antioxidant molecules, we measured TAS, according to the techniques of Erel, as well [ 35 ]. In previous studies, it was suggested that OSI could show the oxidative state more precisely than the sole levels of TOS or TAS [ 40 , 41 ]. Hence, OSI could be regarded as an approximate indicator for identifying Cis-mediated genotoxicity, hepatotoxicity, nephrotoxicity, and preservation provided by NOX in subjects under Cis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, rather than individually determining antioxidant molecules, we measured TAS, according to the techniques of Erel, as well [ 35 ]. In previous studies, it was suggested that OSI could show the oxidative state more precisely than the sole levels of TOS or TAS [ 40 , 41 ]. Hence, OSI could be regarded as an approximate indicator for identifying Cis-mediated genotoxicity, hepatotoxicity, nephrotoxicity, and preservation provided by NOX in subjects under Cis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although a direct comparison of EP efficacy compared to other HMGB1 inhibitors is currently lacking, EP has been safely tested in humans and has been used in clinical trials [ 43 ]. In addition, some preclinical studies have demonstrated that inhibition of HMGB1 release by EP significantly increased the tumor cell sensitivity to other anticancer agents [ 17 ], and also protected against chemotherapy-induced cytotoxicity [ 45 ]. In summary, this evidence supports the possible use of EP as an adjuvant in MM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…21,22,35 Previous studies have suggested that OSI may be a more accurate indicator of oxidative status than single TOS or TAS levels. 36,37 Various chemotherapy agents, such as cisplatin in particular, by leading to excessive oxidant production in the body or weakening of the antioxidant mechanism, have been shown to cause an increase in TOS and OSI and a decrease in TAS. 38 In addition, these parameters have been used as an oxidative stress parameter in various inflammatory skin diseases such as psoriasis and dermatitis.…”
Section: Discussionmentioning
confidence: 99%